The role and place of historical and pedagogical knowledge in the system of traininga modern higher education teacher - Друганова, О. М. (Scientific notes of the pedagogical department, 2019)
The article describes the role and place of historical and pedagogical knowledge in the content of professional training of a modern higher education teacher. The research has proved that the proper place in the content of the course “Pedagogy of Higher School” should be given to the systematic study of the heritage of outstanding pedagogues and scientists whose activities were associated with the founding and development of higher education and schools in Ukraine in different historical periods, in particular during the period of the XIX century. Students’ acquisition of such knowledge will help determine the role of an individual in changing pedagogical paradigms and forming a national and universal component of the modern philosophy of Ukrainian pedagogy (O. Kirdan), develop professionally oriented critical thinking and establish professional culture of a modern higher education teacher. The article pays special attention to the significance of the creative heritage of M. Pyrohov, whose activities significantly influenced the development of national higher education and pedagogy. The paper describes the main theses presented in the scientific works of the enlightener, which have not lost their relevance and can be creatively reconsidered and implemented into the practice of training modern teachers for higher education institutions, including: 1) M. Pyrohov’s views on the significance of the “educational power of an individual” regarded as “the only pledge of true progress”, the role of the teaching staff in the development of education and science, “…whose honor and glory” should “focus on the pursuit of science, the improvement of its course, on active participation in the development and prosperity of the university”; 2) conclusions of the scholar regarding the importance of conducting a competitive selection to replace the professorial vacancies at universities as an effective mechanism for improving the quality of the teaching staff; presentation of the procedure of selecting professors, which should take place under certain conditions, such as submission of a scientific or educational piece of writing (manual or monograph); presentation of at least one immediate student who was expected to have such a level of scientific education that he held or could hold a position of Associate Professor teaching the discipline the professor specialized in or any of the related subjects; 3) ideas on how to improve various forms of organization of higher education training in general and in the practice of lecturing in particular. It has been ascertained that the subject of further scientific research may be related to the study of ways to improve the organization of the educational process in institutions of higher education presented both in domestic and foreign pedagogical thought and practice.